Why is there no philosophy of international relations? - Gałganek, Andrzej (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2019)
Why is there no philosophy of International Relations? Why, despite the significant intellectual and institutional development of International Relations after World War II, has IR failed to generate any ‘grand ideas’ that would influence the broadly understood humanities? None of the theories of international relations indicates the exceptional features of interna- tionality as its foundation. None of these theories formulates a fundamental claim to its subject matter in International Relations the way geography, history or sociology do. This leads to the conviction that international relations do not have to be formed by aspects of the social world that are specific to them, and can be interpreted in terms of ideas imported from the disciplines that deal with examining aspects relevant to them. The basic disadvantage of this openness of International Relations to other disciplines is the lack of reflection on its own ‘deep ontology.’ This seems to be the most important reason for the lack of a philosophy of International Rela- tions. The author accomplishes two basic goals in his text. Firstly, he undermines the legitimacy of the three attitudes prevailing in IR on understanding internationality, which he calls internal- ism, externalism and correlationism. Secondly, he presents the essence and consequences of the negative character of IR, which involves the absence of the philosophy of IR and studying internationality in the same manner as political science does. The author argues that understanding this ‘strange orthodoxy’ can be a means to overcom- ing it, thereby opening up the possibility of conceiving the ontology of IR, or outlining the path leading to the philosophy of International Relations. Finally, the author refers to the proposal of Justin Rosenberg, to then present an idea for an ontology on which the philosophy of Interna- tional Relations could be founded.

Dlaczego nie ma filozofii nauki o stosunkach międzynarodowych? Dlaczego pomimo istotnego intelektualnego i instytucjonalnego rozwoju nauki o stosunkach międzynarodowych po II wojnie światowej, nie wygenerowała ona żadnych „wielkich idei”, które wywarłyby wpływ na szeroko rozumiane nauki humanistyczne? Żadna z teorii stosunków międzynarodowych nie wskazuje jako swojego fundamentu wyjątkowych własności międzynarodowości. Żadna z tych teorii nie formułuje fundacyjnego rosz- czenia do własnego przedmiotu w nauce o stosunkach międzynarodowych na sposób w jaki robią to geografia, historia czy socjologia. Prowadzi to do przekonania, że stosunki międzynarodowe nie muszą być kształtowane przez swoiste dla nich aspekty świata społecznego i można je interpretować za pomocą idei importowanych z dyscyplin, które zajmują się badaniem właściwych dla nich aspektów. Podstawową wadą tej otwartości nauki o stosunkach międzynarodowych na inne dyscypliny jest brak namysłu nad własną „głęboką ontologią”. W tym wydaje się tkwić najważniejsza przyczyna braku filozofii nauki o stosunkach międzynarodowych. Autor realizuje w swoim tekście dwa podstawowe cele. Po pierwsze, podważa zasadność dominujących w NSM stanowisk w kwestii rozumienia międzynarodowości, które nazywa internalizmem, eksternalizmem i korelacjonizmem. Po drugie, przedstawia istotę i konsekwencje negatywnego charakteru NSM polegającego na braku filozofii dyscypliny i badaniu międzynarodowości na wzór nauk politycznych. Autor przekonuje, że zrozumienie tej „dziwnej ortodoksji” może otworzyć drogę do jej przezwyciężenia. Jej pokonanie zaś otworzyć możliwość pomyślenia ontologii NSM, czyli zarysować drogę prowadzącą do filozofii nauki o stosunkach międzynarodowych. Ostatecznie, odwołując się do propozycji J. Rosenberga, przedstawia ideę ontologii, na której można budować filozofię nauki o stosunkach międzynarodowych.
Dlaczego nie ma filozofii nauki o stosunkach międzynarodowych?
Keywords: philosophy of International Relations; internalism; externalism; correlationism; ontology; multiplicity; filozofia nauki o stosunkach międzynarodowych; internalizm; eksternalizm; korelacjonizm; wielość